Novel imaging of the prostate reveals spontaneous gland contraction and excretory duct quiescence together with different drug effects. Issue 3 (3rd January 2018) - Kügler, Robert; Mietens, Andrea; Seidensticker, Mathias; Tasch, Sabine; Wagenlehner, Florian M.; Kaschtanow, Andre; Tjahjono, Yudy; Tomczyk, Claudia U.; Beyer, Daniela; Risbridger, Gail P.; Exintaris, Betty; Ellem, Stuart J.; et al.
Abstract : Prostate carcinoma and benign prostate hyperplasia (BPH) with associated lower urinary tract symptoms (LUTS) are among the most prevalent and clinically relevant diseases in men. BPH is characterized by an en‐ largement of prostate tissue associated with increased tone of smooth muscle cells (SMCs) which surround the single glands composing the prostate. Secretions of the glands leave the prostate through local excretory ducts during the emission phase of ejaculation. Pharmacological treatment of BPH suggests different local drug targets based on reduction of prostate smooth muscle tone as the main effect and disturbed ejaculation as a common side effect. This highlights the need for detailed investigation of single prostate glands and ducts. We combined structural and functional imaging techniques—notably, clear lipid‐exchanged, acrylamide‐hybridized rigid imaging/immunos‐ taining/ insitu hybridization‐compatible tissue‐hydrogel (CLARITY) and time‐lapse imaging—and defined glands and ducts as distinct SMC compartments in human and rat prostate tissue. The single glands of the prostate (comprising the secretory part) are characterized by spontaneous contractions mediated by the surrounding SMCs, whereas the ducts (excretory part) are quiescent. In both SMC compartments, phosphodiesterase (PDE)‐5 is expressed. PDE5 inhibitors have recently emerged as alternative treatment options for BPH. We directly visualized that the PDE5 inhibitors sildenafil and tadalafil act by reducing spontaneous contractility of the glands, thereby reducing the muscle tone of the organ. In contrast, the ductal (excretory) system and thus the prostate's contribution to ejaculation is unaffected by PDE5 inhibitors. Our differentiated imaging approach reveals new details about prostate function and local drug actions and thus may support clinical management of BPH.—Kügler, R., Mietens, A., Seidensticker, M., Tasch, S., Wagenlehner, F. M., Kaschtanow, A., Tjahjono, Y., Tomczyk, C. U., Beyer, D., Risbridger, G. P., Exintaris, B., Ellem, S. J., Middendorff, R. Novel imaging of the prostate reveals spontaneous gland contraction and excretory duct quiescence together with different drug effects. FASEB J. 32, 1130‐1138 (2018). www.fasebj.org